The Implementation of the Teaching at The Right Level (TaRL) Approach through Differentiated Instruction to Improve Narrative Text Learning Outcomes among Grade XI-8 Students at SMAN 17 Surabaya - Safira Aqila; Wijayadi; Nur Fitriah (PROCEEDING UMSURABAYA, 2026)
This study aims to describe the effectiveness of implementing differentiated instruction through the Teaching at The Right Level (TaRL) approach to improve Narrative Text learning outcomes among Grade XI-8 students at SMAN 17 Surabaya. The research method employed was Classroom Action Research (CAR) conducted in two cycles, involving 23 students as subjects. Data were collected through diagnostic assessment, observation, and student reflection. The results showed an increase in the average student score from 53.91 (pre-test) to 85.22 (post-test). As many as 60.87% of students experienced a very significant improvement, 17.39% significant, 13.04% moderate, and only 8.7% showed no improvement. The implementation of TaRL-based differentiated instruction proved effective in meeting diverse learning needs, increasing motivation, participation, and student achievement in Narrative Text material. The implications of this research emphasize the importance of continuous assessment and adaptive teaching strategies to optimize students’ potential